The influence of surface characteristics on the tribological interactions at the shoe-surface interface in tennis - Clarke, J.; Carré, M.; Damm, L.; Dixon, S. (Procedia Engineering, 2012)
During dynamic tennis specific movements, such as accelerating and side stepping, the traction provided by a shoe-surface combination plays an important role in the injury risk and performance of the player. Acrylic hard court tennis surfaces have been reported to have increased injury occurrence due to an increased traction coefficient. There is a requirement for an improved scientific understanding of the tribological interactions at the shoe surface interface and the effects footwear and surface parameters have on the friction mechanism developed. Often mechanical test methods used for the testing and categorisation of playing surfaces do not tend to simulate loads occurring during participation on the surface, and thus are unlikely to predict human response to the surface. A new traction testing device, discussed in this paper, has been developed to mechanically measure the traction force between the shoe and the surface under appropriate loading conditions. Acrylic Harcourt tennis surfaces generally have a rough surface topography, due to a sand and acrylic paint mixed top coating, and have a deformable under layer to provide impact attenuation. Surface micro-roughness has been found to influence the friction mechanisms presents during viscoelastic contacts, as found in footwear-surface interactions. This paper aims to further understand the influence of micro-roughness on tennis surfaces. The micro-roughness and traction of a controlled set of acrylic hard court tennis surfaces have been measured. The influence of roughness on tennis surfaces traction is discussed.